Цаг үе ба метафорчлах сэтгэлгээ - Ц.Магсар, (Acta Mongolica, 2013)
The article comments some ideas of George LakofT and Mark Johnson's work ''Metaphors We Live By" became a new trend of theoretical research in last thirty years of metaphor studies and it analyzes hou the metaphor reflects the current social circumstances in Mongolia. Mongolian language incorporates rich metaphors as many other languages, however, research work in terms of their structure and cognition is occasional. Tlie author has observed and exemplified some metaphors applicable in social and political frames that are widely used in Mongolian journalism and developed a relevant thematic classification in his article. By his article, author suggests that further development of cognitive researches on metaphors is recommended in future literature studies and pragmatic linguistics.